Coffee and type 2 diabetes risk: Is the association mediated by adiponectin, leptin, c‐reactive protein or Interleukin‐6? A systematic review and meta‐analysis. Issue 6 (21st January 2021) - Osama, Hasnaa; Abdelrahman, Mona A.; Madney, Yasmin M.; Harb, Hadeer S.; Saeed, Haitham; Abdelrahim, Mohamed E. A.
Abstract: Aim: Coffee and diabetes risk association has been demonstrated in numerous studies; however, the exact mechanism has not been clarified yet. The present meta‐analysis was conducted to cover the current knowledge regarding the effect of coffee on Type 2 Diabetes (T2D), in addition to the evaluation of adiponectin, leptin, C‐reactive protein (CRP) and Interleukin‐6 (IL‐6) levels among coffee consumers as relatively possible mediators of this effect. Method: A comprehensive search of the literature was carried out using search engines up to March 2020. The effect sizes were investigated using the standardised mean difference (SMD) and odds ratios (OR) or relative risk (RR) with its 95% confidence interval (CI). A total of 69 cross‐sectional and cohort studies were included and divided as follows: 31 articles for T2D risk, 15 studies for adiponectin, 6 studies for leptin, 12 studies for CRP and 5 studies for IL‐6. Results: Overall, coffee consumption was inversely associated with T2D risk with an estimated pooled RR of 0.73 (95% confidence interval [0.68, 0.80] for the highest vs lowest coffee consumption categories. The combined SMD between the different coffee intake categories, showed that coffee consumption was associated with higher adiponectin levels ( P  = .002), and lower level of leptin ( P  = .04) and CRP ( P  = .2), with apparently no change in IL‐6 levels ( P  = .91). Conclusion: The present meta‐analysis showed strong epidemiological evidence that coffee consumption is inversely associated with the risk of T2D. Also, adiponectin, leptin concentrations appeared to be potential mediators of the coffee effect on diabetes, while IL‐6 levels did not.